Restorasi dan Revitalisasi Pasca Degradasi Ekosistem Mangrove di Paluh Merbau Kabupaten Deli Serdang - Meilinda Suriani Harefa; Adeline Adeline; Feby Cyntia Silalahi; Michael Austin Lambue Panjaitan (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
This study aims to determine restoration and revitalization efforts after the degradation of mangrove ecosystems in Paluh Merbau. The observation method is direct observation of the mangrove area. The results show that the mangrove ecosystem is fragile and sensitive to change. Mangrove forest degradation in Paluh Merbau has been very severe; much mangrove vegetation has fallen due to being unable to withstand abrasion and sedimentation in coastal waters and continues to experience area shrinkage. Restoration and revitalization of the Paluh Merbau mangrove ecosystem were carried out by naming Rhizapora apiculata, Rhizapora stylosa, and Avicennia marina.